Testing the Educational Screening Hypothesis - Riley, John G. (Journal of Political Economy, 1979)
Human capital theorists have traditionally argued that individuals invest in education until the marginal gain in productivity is equal to the marginal opportunity cost. However, the observed correlations among income, education, and ability measures are also consistent with education being used to screen for exogenous ability differences. This paper tests for such an informational role, arguing that screening will be much more important in some occupations than in others. Subsamples of "screened" and "unscreened" occupations are isolated and compared. It is concluded that observed differences, not readily explained by the traditional model, are consistent with the educational screening hypothesis.